Amino Acid-Doped Polyaniline Nanotubes as Efficient Adsorbent for Wastewater Treatment - Zhao Zhao; Yimin Yang; Longfei Xu; Zihan Qiu; Ziheng Wang; Yongfeng Luo; Kun Du (Journal of Chemistry)
A natural amino acid-doped polyaniline nanostructure was prepared by a simple in situ chemical polymerization method in an aqueous medium. The structure and morphology of composite material were characterized by FESEM, TEM, FT-IR, and XRD. The results showed that the product possesses a large aspect ratio and a hollow tubular morphology. As-synthesized products were further applied to remove dyes and heavy metal ions from the aqueous solution, which exhibited good removal capacity toward Congo red (955.6 mg·g−1) and Cr(VI) (60.0 mg·g−1). The adsorption data for the former were found to be well described by the pseudo-first-order kinetic and Langmuir adsorption isotherm model. Thermodynamic studies show that the adsorption of Congo red by GluP is a spontaneous and endothermic process. Moreover, cyclic experiment results show that the polyaniline composites exhibited good recyclability. Therefore, these amino acid-doped polyaniline nanotubes can be expected to be an ideal candidate for the removal of organic dye and heavy metal ions from wastewater.